2015
DOI: 10.1007/s13760-015-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rehabilitation in multiple sclerosis relapse on fatigue, self-efficacy and physical activity

Abstract: Relapse of disease is one of the most prominent characteristics of multiple sclerosis. Effectiveness of rehabilitation programmes on fatigue, self-efficacy (SE) and physical activity (PA) has not been investigated so far in context of relapse. The aim of our study was to examine if rehabilitation programme in addition to high-dose methylprednisolone (HDMP) during relapse of disease can influence fatigue, SE and PA more than corticosteroid therapy alone. Patients were randomized in control group receiving only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The study also suggested that MDR was effective in improving the clinical status of patients with NMOSD in terms of impairments. In the UC group, the EDSS score did not change at 4 weeks and improved at 3 months, which indicated that patients with MNOSD are taking corticosteroids (1 month) and exhibit a certain degree of self-healing ability (3 months) (17). The EDSS score improved at 4 weeks after treatment in the MDR group, which indicated that rehabilitation treatment promotes or speeds up the patient's recovery process.…”
Section: Discussionmentioning
confidence: 94%
“…The study also suggested that MDR was effective in improving the clinical status of patients with NMOSD in terms of impairments. In the UC group, the EDSS score did not change at 4 weeks and improved at 3 months, which indicated that patients with MNOSD are taking corticosteroids (1 month) and exhibit a certain degree of self-healing ability (3 months) (17). The EDSS score improved at 4 weeks after treatment in the MDR group, which indicated that rehabilitation treatment promotes or speeds up the patient's recovery process.…”
Section: Discussionmentioning
confidence: 94%
“…The rehabilitation of the MS patients is necessary but also very complex, it requires a personalized and multidisciplinary care. The modern medical treatment is not the only way that can postpone the progressive neurodegenerative processes and still remains unclear up to where this treatment prevents the loss of the functional abilities (Nedeljkovic U et al, 2015).…”
Section: Clinical Trial and Literature Reviewmentioning
confidence: 99%
“…The authors reported an improvement of quality of life, physical activity and self-efficacy in PwMS measured at 1 and 3 months post-relapse in favour of the group who received the multidisciplinary rehabilitation. 5,6 In addition, no negative or adverse effects were reported in the group who received the multidisciplinary rehabilitation. 5,6 Furthermore, it is noteworthy to mention evidence provided by retrospectively studies, which reported beneficial effects of postrelapse inpatient rehabilitation in PwMS.…”
mentioning
confidence: 91%
“…To our best knowledge, three studies applying a randomised control trial design assessed the effects of post-relapse rehabilitation in PwMS following an acute relapse. [5][6][7] In all three studies, this was provided as multidisciplinary rehabilitation, although with differences in structure and content.…”
mentioning
confidence: 99%
See 1 more Smart Citation